Gerenciamento de projetos de produtos nas micro e pequenas empresas sustentáveis - Carvalho, Yeda Alves de (2020)
This work to highlights the importance of Micro and Small Enterprises (MSEs) in the Brazilian context. As well as the importance of the challenges that sustainable micro and small companies face to be efficient in their product development projects. This study aims to understand how micro and small sustainable companies manages their product projects. Companies are considered sustainable when they adopt practices, attitudes or obey principles that make their activities meet the needs of the current generation without compromise as the needs of future generations. This study is of a qualitative nature, with an exploratory methodological approach, that is, a basic qualitative study. The study focused on micro and small sustainable Brazilian companies, where the data collection instrument used was an interview script and a consultation of documents from secondary data sources. MAXQDA software was used to support data analysis. The results presented as MSEs manage their product projects in an intuitive way without much formalization. They face barriers to manage efficiently and still follow their values when it comes to sustainability. As studied MSEs undergo financial restrictions, which prevent them from hiring professionals specialized in project management and other specific areas on demand. In addition to dealing with the lack of commitment in terms of delivery times by their raw material suppliers or manufacturers when manufacturing is outsourced. This work contributes to the literature suggesting less bureaucratic processes, which require little or no financial investment, which are simple enough to be used by professionals who are not specialized in project management, another suggestion would be the inclusion of sustainable project management in educational plans in management courses. Inclusion of MSEs in studies involving project management. This study identifies the key elements necessary to develop an analysis model in relation to the aspects that characterize a company as being sustainable.